Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/15592294.2017.1367475
|View full text |Cite
|
Sign up to set email alerts
|

Variability of genome-wide DNA methylation and mRNA expression profiles in reproductive and endocrine disease related tissues

Abstract: Genome-wide association studies in the fields of reproductive medicine and endocrinology are yielding robust genetic variants associated with disease. Integrated genomic, transcriptomic, and epigenomic molecular profiling studies are common methodologies used to understand the biologic pathways perturbed by these variants. However, molecular profiling resources do not include the tissue most relevant to many female reproductive traits, the endometrium, while the parameters influencing variability of results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 67 publications
(57 reference statements)
6
39
0
Order By: Relevance
“…After a linear reduction of the variability for more than 30000 expressed genes, the control samples cluster together in a small group. The dispersion of the samples in the PCA analysis is lower compared to other tissue expression profiles using the same exploratory analysis [61]. In contrast, PTB chorioamniotic expression analysis revealed a more diverse group, further stressing the heterogeneity of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…After a linear reduction of the variability for more than 30000 expressed genes, the control samples cluster together in a small group. The dispersion of the samples in the PCA analysis is lower compared to other tissue expression profiles using the same exploratory analysis [61]. In contrast, PTB chorioamniotic expression analysis revealed a more diverse group, further stressing the heterogeneity of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Variability between lesions within person has been well-documented 16 and future research should investigate variability of DNAm age between lesions within an individual. While all of the lesions studied here were endometriomas, peritoneal disease presents with different colored lesions that are thought to represent a continuum from younger to older disease 25 , a hypothesis that could be explored using DNAm age.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found a correlation of 0.8 between DNAm age and chronological age in uterine endometrium when all of the samples came from the same menstrual time point (LH+7, or 7 days after the surge in luteinizing hormone) 15 , but our correlation was unchanged if we stratified by menstrual phase (LH+8), or by endometriosis status. We next tested the effect of menstrual phase on DNAm age because menstrual phase is known to affect DNA methylation 16 . Each of the healthy controls donated two samples, one during the early secretory phase and the second during mid-secretory phase of the same menstrual period 17 .…”
Section: Endometriosis Does Not Affect Dna Methylation Age Of Eutopicmentioning
confidence: 99%
“…FENOX was built on experience and feedback we received from patients and research nurses during a previous study (a study to identify possible biomarkers in women with Endometriosis at Oxford18). In addition, the research objectives were set in accordance with research priorities identified through the James Lind Alliance Priority Setting Partnership (PSP) for endometriosis, in which we participate 19.…”
Section: Methods and Analysismentioning
confidence: 99%
“…As this is a prospective sample and data collection study, there is no randomisation of patients as all women will undergo surgery as part of their routine clinical management. As previously,18 we will use SPSS, GraphPad Prism, STATA and R for analysis, and employ t-tests, analysis of variance (ANOVA), correlation coefficient analysis and similar methods. We plan to use multivariate logistic regression models in comparisons of endometriosis cases with controls, and fibroid cases with controls, adjusting for confounders relevant to the hypothesis being tested.…”
Section: Interventionsmentioning
confidence: 99%